Achilles tendon detachment after local infiltration of corticosteroids: a case report - Del Vecchio, Jorge; Dealbera, Eric; Batista, Jorge; Ghioldi, Mauricio; Chemes, Lucas (Journal of the Foot & Ankle, 2021)
Complete disinsertion of the Achilles tendon is relatively rare but is an injury of considerable clinical significance. A 50-year-old non-smoking man presented with complete disinsertion of the Achilles tendon due to an indirect low-energy trauma shortly after administration of local corticosteroid injections (LCI) for treatment of deep retrocalcaneal bursitis. Imaging studies showed complete disinsertion of the Achilles tendon as well as severe Haglund syndrome and retrocalcaneal bursitis. The tendon was repaired, and the Haglund deformity and retrocalcaneal bursa were then resected. Although Achilles tendon rupture is a frequent complication after LCI, to date, no cases of disinsertion have been published. Surgeons must be aware of this issue, especially in patients with previous insertional calcific Achilles tendinosis and Haglund syndrome. Level of Evidence V; Therapeutic Studies; Expert Opinion.